Estimação da alíquota de imposto indireto ótimo sobre o consumo usando o modelo de Deaton no Brasil - Badagnan, Thaisa França (2011)
Taxes on production and movement of goods are one of the largest sources of tax revenue in Brazil. A tax system with characteristic of e ciency and equity allows the Government, both a better redistribution of income as achieving revenue needed to cover his expenses; with the lowest possible cost in terms of e ciency. Optimal tax models use economic analysis to evaluate the fairness and e ciency of a tax system. The goal here is to obtain optimal tax rates on consumption in Brazil. It estimates optimal tax rates using the methodology introduced by Deaton (1977). For such data were from POF 2002/2003. The results of this work show that the tax structure should be characterized by selectivity of aliquots. Medicines for having greater participation in the income of the poorest are subsidized; on the other hand, foods are not subsidized, but receive a low rate of tax.